Adult-plant resistance to Puccinia recondita f. sp. tritici in a collection of wild Triticum species - Barnard, Johanna Elizabeth (University of the Free State, 1999)
The ability of rust pathogens to mutate and form new and virulent races, necessitates the broadening of the genetic base of resistance in common wheat to rust diseases. The wild relatives offer a rich reservoir of resistance genes. In an attempt to identify new sources of resistance to Puccinia recondita f. sp. tritici, 353 Triticum accessions, comprising diploid, tetraploid and hexaploid species were evaluated for seedling and adult-plant resistance to a mixture of pathotypes UVPrt2, 3, 9, and 13. In addition to infection type studies, plant height, growth habit and head type of adult plants were also recorded. One hundred and twenty six of the accessions were resistant to moderately resistant as seedlings to the pathotype mixture, whereas 180 were resistant or moderately resistant as adult plants. The number of days from planting to flag leaf stage varied from 54 to 187. High levels of resistance were observed in adult plants of T. longissimum, T. sharonense, T. searsii and T. turgidum ssp. compactum. Triticum kotschyi and T. ventricosum expressed hypersensitive infection types. Partial resistance (small pustules without any apparent chlorosis), was observed in T. turgidum ssp. durum, T. turgidum ssp. pyramidale and T. tauschii. In T. turgidum, which comprised 14 subspecies and 272 accessions, approximately 44% of the adult plants were resistant to moderately resistant compared to 24% of the seedlings. According to these results 13 accessions, producing smaller or fewer leaf rust pustules, without the characteristic chlorosis and necrosis associated with hypersensitive resistance, were selected. Adult plants were quantitatively inoculated with pathotype UVPrt13 of P. recondita f. sp. tritici. Palmiet, a bread wheat cultivar susceptible to UVPrt13, was included as a control. Latent period of leaf rust, uredium size and density, and infection type were determined in two experiments. In the first experiment latent period ranged from 309 h to 401 h compared to 258 h in the susceptible control, Palmiet. In the second experiment Palmiet had a latent period of 244 h whereas those in the Triticum accessions ranged between 175 hand 372 h. Most accessions supported more uredia per ern" flag leaf surface than Palmiet in the first, but not in the second experiment. However, pustules were significantly smaller on most of the lines. Based on these components, T. timopheevii ssp. araraticum v. tumanianii, T. turgidum ssp. durum v. obscurum, and T. turgidum ssp. persicum v. stramineum, showed high levels of partial resistance. Triticum turgidum and T. timopheevii accessions rated as potentially valuable sources of resistance were selected for histological studies on mechanisms of resistance. Penetration and establishment of the leaf rust pathogen were studied in flag leaves of T. timopheevii, T. turgidum ssp. dicoccum, T. turgidum ssp. durum and T. turgidum ssp. compactum. The T. aestivum wheats Thatcher (Tc) (susceptible common wheat control) and TcLr19 (resistant common wheat control) were included in the experiment. Using fluorescence microscopy, infection sites of pathotype UVPrt13 were examined for the percentage prestomatal exclusion (germtubes not forming appressoria and appressoria not forming over stomata), abortive penetration (non penetrating appressoria and aborted substomatal vesicles), early abortion (six or less haustorium mother cells per infection site) and infection sites successfully culminating in colonies. Flag leaf sections were prepared for phase-contrast microscopy by staining with either Trypan blue alone or in combination with a solution of picric acid in methyl salicylate. To confirm and expand light microscopy observations, upper and inner surfaces of epidermal tissue of T. timopheevii and T. turgidum ssp. dicoccum were fixed and prepared for scanning electron microscopy. Observations showed that resistance in T. timopheevii was typically hypersensitive and may thus not be durable. The prehaustorial resistance exhibited in T. turgidum ssp. durum and T. turgidum ssp. compactum, may be valuable sources of nonhypersensitive resistance when transferred to cultivated wheat.

Die vermoë van roespatogene om te muteer en nuwe, virulente rasse te vorm, het 'n voortdurende behoefte aan nuwe weerstandsbronne tot gevolg. Kiemplasma van wilde spesies verwant aan broodkoring is 'n potensiële bron van weerstandsgene. In'n poging om nuwe weerstandsbronne teen Puccinia recondita f. sp. tritici te identifiseer, is 353 Triticum inskrywings vir weerstand geëvalueer. Die inskrywings het bestaan uit diploïede, tetraploïede en heksaploïede tipes en is getoets teen die patotipes UVPrt2, 3, 9 en 13. Benewens infeksietipe is planthoogte, groeiwyse en aartipe bepaal. Eenhonderd- ses-en-twintig inskrywings was matig-weerstandbiedend tot volkome weerstandbiedend tot volkome weerstandbiedend in die volwasse stadium. Die aantal dae vanaf plant tot die vlagblaarstadium het gewissel tussen 54 en 187. Hoë vlakke van weerstand is gevind in T. longissimum, T. sharonense, T. searsii en T. turgidum ssp. compactum. Triticum kotschyi and T. ventricosum het hipersensitiewe infeksietipes getoon. Gedeeltelike weestand (klein puisies sonder chlorose) is gevind in T. turgidum ssp. durum, T. turgidum ssp. pyramidale en T. tauschii. In T. turgidum, bestaande uit 14 subspesies and 272 inskrywings, was ongeveer 44% volkome weerstandbiedend tot matig-weerstandbiedend as volwasse plante teenoor 24% in die saailingstadium. Na aanleiding van bogenoemde resultate is 13 inskrywings geselekteer. Hierdie inskrywings het nie chlorotiese of nekrotiese reaksies, soos normaalweg geassosieër met hipersensitiwiteit, getoon nie. Volwasse plante is kwantitatief geïnokuleer met patotipe UVPrt13 van P. recondita f. sp. tritici. Palmiet is ingesluit as vatbare kontrole. Latente periode van blaarroes, urediumgrootte en -digtheid en infeksietipe is bepaal. Die eksperiment is in sy geheel herhaal. In die eerste eksperiment het latente periode in die inskrywings tussen 309 h en 401 h gevarieër, in teenstelling met 258 h in Palmiet. In die tweede eksperiment het Palmiet 'n latente periode van 244 h getoon. Latente periode in die inskrywings het gewissel tussen 175 h en 372 h. In meeste van die inskrywings is hoër urediumdigthede aangeteken as op Palmiet, hoewel puisies in die spesie-aanwinste meestal kleiner was. Gebaseer op bogenoemde resultate, beskik T. timopheevii ssp. araraticum v. tumanianii, T. turgidum ssp. durum v. obscurum, en T. turgidum ssp. persicum v. stramineum, oor hoë vlakke van gedeeltelike weerstand. Weerstandsmeganismes is histologies bestudeer in inskrywings van T. turgidum en T. timoph.eevii. Penetrasie deur en vestiging van die patogeen is bestudeer in vlagblare van T. timopheevii, T. turgidum ssp. dicoccum, T. turgidum ssp. durum en T. turgidum ssp. compactum. Die broodkoring-kultivars Thatcher (vatbare kontrole) en TcLr19 (weerstandbiedende kontrole) is ingesluit. Fluoressensie mikroskopie is gebruik om infeksiepunte te bestudeer en die persentasie prestomatale uitsluiting (kiembuise wat nie appressoria vorm nie, of nie-stomatale appressoria), abortiewe penetrasie (niepenetrerende appressoria of abortiewe substomatale vesikels), vroeë abortering (ses of minder haustoriumoederselle per infeksiepunt) en infeksiepunte wat kolonies vorm, is genoteer. Blare is ook gekleur met trypanblou en 'n versadigde oplossing van pikriensuur in metielsalisilaat. Om die vorming van infeksiestrukture op en in blaarweefsel van T. timopheevii and T. turgidum ssp. dicoccum te bestudeer, is hipersensitiewe reaksie getoon en dié weerstand is moontlik nie volhoubaar nie. Die prehaustoriale weerstand in T. turgidum ssp. durum and T. turgidum ssp. compactum kan moontlik waardevolle bronne van nie-hipersensitiewe roesweerstand wees.
Dissertation (M.Sc.Agric. (Plant Pathology))--University of the Free State, 1999
Keywords: Wild wheats|xDisease and pest resistance; Leaf rust of wheat